Enatioselective Rotation of Chiral Particles by Azimuthally Polarized Beams. Issue 10 (5th October 2022) - Li, Manman; Chen, Xu; Yan, Shaohui; Zhang, Yanan; Yao, Baoli
Abstract : Chiral Particles Although the focused azimuthally polarized beam carries no optical chirality, it can produce different effects with paired enantiomers, and it can drive the orbital rotation of chiral spherical particles even though it does not carry optical orbital angular momentum, enabling optical chiral separation and identification. More details about this study can be found in article number 2200117 by Baoli Yao and co‐workers.